Tommy Tricker and the Stamp Traveller [videorecording (DVD)] - Rubbo, Michael; Evans, Lucas; Rogers, Anthony; Stanely, Jill (Hen's Tooth Video, 2006)
After trading away one of his father's most precious stamps, Ralph begins his desperate mission to find a replacement. He finds himself on a magical journey aboard a postage stamp headed for Australia, with an unexpected stop in China.